Марсианские войны: перевод с английского / Э. Берроуз - Берроуз Эдгар Райс (Приключения и фантастика, 2006)
Экземпляры: ф14/28 (20250114) / Инвентарный номер: 43458 / Цена: 102.10 / Сис.шифр: И(англ)ср / Авт.знак: Б 51 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)